2015
DOI: 10.1073/pnas.1414550112
|View full text |Cite
|
Sign up to set email alerts
|

Social status modulates prosocial behavior and egalitarianism in preschool children and adults

Abstract: Humans are a cooperative species, capable of altruism and the creation of shared norms that ensure fairness in society. However, individuals with different educational, cultural, economic, or ethnic backgrounds differ in their levels of social investment and endorsement of egalitarian values. We present four experiments showing that subtle cues to social status (i.e., prestige and reputation in the eyes of others) modulate prosocial orientation. The experiments found that individuals who experienced low status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 52 publications
9
151
6
2
Order By: Relevance
“…These individuals frequently focus on increasing their payouts while neglecting others' payouts. These tendencies can be observed early in ontogeny: Compared to their low-rank counterparts, five-year-old children who were in a high-rank position gave fewer stickers to a child in need (Guinote et al 2015). This was true regardless of whether rank was determined by dominance or was experimentally induced.…”
Section: Does Power Corrupt?mentioning
confidence: 96%
See 2 more Smart Citations
“…These individuals frequently focus on increasing their payouts while neglecting others' payouts. These tendencies can be observed early in ontogeny: Compared to their low-rank counterparts, five-year-old children who were in a high-rank position gave fewer stickers to a child in need (Guinote et al 2015). This was true regardless of whether rank was determined by dominance or was experimentally induced.…”
Section: Does Power Corrupt?mentioning
confidence: 96%
“…Furthermore, with enhanced perceived control, powerful people perceive the self as an independent, self-sufficient entity (independent self-construal). In contrast, powerless people resort to relationships as a means to enhance control, are more communal, and have an interdependent self-construal (see Fiske & Dépret 1996, Guinote et al 2015, Guinote & Chen 2016.…”
Section: Power and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these themes is certainly the effect of social class on prosociality. Recent social psychological research has presented evidence of a negative effect of social class on several prosocial behaviors [1][2][3]. In these studies, higher class individuals were found to be less charitable, less trusting, less generous, and less helpful than lower social class individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Des enfants issus de cultures ou de familles dont la structure est verticale, ou des enfants qui occupent un rang hiérarchique plus élevé dans leur classe pourraient être plus enclins à renforcer l'asymétrie qui se présente à eux, en accordant plus de ressources au dominant. À cet égard, une étude a récemment montré qu'une modification ponctuelle du statut social de l'enfant influençait sa volonté de partager des ressources [26] : les enfants ayant le statut le plus élevé (ils étaient parvenus à obtenir un jouet particulièrement attractif) étaient moins enclins à partager des autocollants que leur donnait l'expérimentateur que les enfants de plus bas statut (ils avaient dû se contenter du jouet le moins attractif). Les résultats exposés ici montrent qu'à un âge assez précoce, les enfants peuvent se représenter les désavantages associés à la subordination.…”
Section: Controverses Et Perspectivesunclassified